Sensorimotor control is impaired in dancers with functional ankle instability. - Hiller, C; Refshauge, K; Beard, D (2004)
BACKGROUND: Factors potentially causing chronic instability after ankle inversion sprains have rarely been examined during the injuring movement. PURPOSE: To compare control of ankle movement during quiet stance and after inversion perturbation in chronically unstable ankles (n = 16) with healthy controls (n = 26). METHODS: Movement control was measured as magnitude of lateral ankle oscillation, using 3SPACE Fastrak during single leg stance (baseline oscillation) in two foot positions, flat and demi-pointe. In both positions, time to resume baseline oscillation after inversion perturbation (perturbation time) of 15 degrees for the flat foot and 7.5 degrees on demi-pointe was also determined. RESULTS: Baseline oscillation on demi-pointe was significantly smaller (P < 0.005) for the sprained group (2.5 +/- 0.5 mm) than for controls (4.0 +/- 2.3 mm). Perturbation time for the flat foot was significantly longer (P < 0.05) for the sprained group (2.2 +/- 0.4 seconds) than for controls (1.8 +/- 0.5 seconds). However, failure rate was higher (P < 0.05) among the sprained group than controls for perturbation with the foot flat and baseline oscillation on demi-pointe. CONCLUSIONS: Findings demonstrated altered sensorimotor control in chronically unstable ankles. Those sprainers who successfully completed the tasks minimized oscillation. The impairments in the sprained group may reflect deficits in either movement detection, peroneal muscle response, or both.